A positive feedback loop of IL-17B-IL-17RB activates ERK/β-catenin to promote lung cancer metastasis. (28th May 2018) - Yang, Yi-Fang; Lee, Yi-Chen; Lo, Steven; Chung, Yi-Ning; Hsieh, Ya-Ching; Chiu, Wen-Chin; Yuan, Shyng-Shiou F.
Abstract: Inflammation contributes to the development and progression of cancer. Interleukin-17 (IL-17) is an inflammatory cytokine that functions in inflammation and cancer, as well as several other cellular processes. In this study, we investigated the roles and the prognostic value of IL-17 and the IL-17 receptor (IL-17R) in lung cancer. Gene expression microarray analysis followed by Kaplan-Meier survival curve showed that IL-17B was associated with poor patient survival, and IL-17B receptor (IL-17RB) was up-regulated in lung cancer tissue compared with normal tissue. Expression of IL-17RB was associated with lymph node metastasis and distant metastasis, as well as poor patient survival. IL-17RB overexpression significantly increased cancer cell invasion/migration and metastasis in vitro and in vivo . IL-17RB induced ERK phosphorylation, resulting in GSK3β inactivation and leading to β-catenin up-regulation. IL-17RB also participated in IL-17B synthesis via the ERK pathway. IL-17RB activation is required for IL-17B-mediated ERK phosphorylation. Taken together, IL-17B-IL-17RB signaling and ERK participate in a positive feedback loop that enhances invasion/migration ability in lung cancer cell lines. IL-17RB may therefore serve as an independent prognostic factor and a therapeutic target for lung cancer. Highlights: Up-regulated of IL-17RB correlates with poor clinical outcomes in lung cancer. IL-17RB overexpression increased lung cancer cell invasiveness and metastasis. IL-17RB activation is required for IL-17B-mediated ERK phosphorylation. IL-17RB participated in IL-17B synthesis via the ERK pathway.